Spatial Synergism a Planning Instrument Sustainable Tourism Village - Jamaluddin Jahid; IKG Bendesa; Syamsul Alam Paturusi; Nyoman Sunarta (Social Impact Journal, 2023)
This study aims to: 1) identify factors that can facilitate the occurrence of spatial synergism in tourism villages, and 2) find and determine the level of undesirable conditions and conditions expected from spatial synergism in tourism villages. Research data were collected using in-depth interviews and using nominal group technique (NGT. Key informants are 5 people and respondents are 15 people determined based on purposive sampling. All data were analyzed with a qualitative analysis approach. The results of the study found that the historical similarity factor, the proximity factor, the hereditary similarity factor, the solidarity factor, the potential similarity factor, and the problem similarity factor are factors that influence the occurrence of spatial synergism in tourism villages. In addition, it was also found that the level of conditions expected from the spatial synergy of tourism villages is to have one plan, one region, one organization, one regulation, and one management. While the level of conditions that are not desirable from the spatial synergism of the tourism village is that it does not have planning (spatial and non-spatial) and professional managers or institutions, sectoral egos appear and discriminatory treatment, disrupts or limit local community activities and culture, does not involve the role of Penta helix tourism actors, carrying out unfair competition in tourism promotion and not using digital technology. This study suggests that a more in-depth study is carried out regarding spatial synergism, especially the process of spatial synergism.